Beta-Carotene Retention and Consumer Acceptability of Selected Products Made from Two Provitamin-A Maize Varieties - Victor Munkhuwa; Kingsley Masamba; William Kasapila (International Journal of Food Science)
A study was carried out to determine beta-carotene retention and acceptability of selected products made from two provitamin-A maize varieties grown in Malawi, namely, MH43A and MH44A. Beta-carotene retention in the provitamin-A maize products was determined by using a “completely randomised block design” (CRBD) whereby the maize varieties (replicates) were treated as fixed blocks, and similar treatments (analytical tests) were applied in each block. Acceptability of the provitamin-A maize products was determined in 6 to 23-month-old children and their caregivers using a cross-sectional design. Results showed that in three maize products, namely, porridge, maize meal, and fermented maize beverage, there was an increase in beta-carotene, with apparent retentions of 111.13%, 170.27%, and 138.22% for MH43A and 156.50%, 207.13%, and 126.17% for MH44A varieties, respectively. Results on pregerminated maize flour produced from MH43A and MH44A maize varieties showed lower beta-carotene apparent retention values of 63.3% and 84.7%, respectively. Results on acceptability showed that most of the caregivers (47.1%) preferred porridge prepared from MH43A flour compared to porridge prepared from MH44A (30.6%) and the control variety (MH26-white maize) (22.4%). For roasted maize, roasted white maize grains (49.6%) were more preferred compared to the two provitamin-A varieties. Results on acceptability with respect to children showed that most children (63.5% and 53.7%) who tested MH43A and MH44A porridge, respectively, consumed all the porridge. Results from this study have shown that there is a high acceptability of provitamin-A maize porridges amongst children prepared from MH43A (55.5%) and MH44A (51.9%) maize varieties. The study therefore recommends that provitamin-A maize varieties should be promoted through appropriate preparation methods that ensure high beta-carotene retention to address vitamin-A deficiency.